Sosialisasi Penerapan Ergonomi pada Pegawai Rumah Sakit - Aulia, Astrina; Miftahurrahmi Fitri; Sherly Nasiva Azari; Diyatul Rohmi; Jeki Rizardi Fanjari; Anggi Syafitri; Dwi Ananda Safitri (Universitas Alifah Padang, 2024)
Hospitals as one of the organizations and/or workplaces that have a high risk of various accidents and Occupational Diseases including ergonomic hazards. Ergonomic hazards are one of the dominant factors found in hospitals that can disrupt worker activities and increase absenteeism. Many studies have been conducted in hospitals related to ergonomic problems that cause complaints of Musculoskeletal Disorders (MSD’s) and Low Back Pain (LBP). The purpose of this service is to provide information on the proper application of ergonomics to both medical and non-medical workers. The method used is counseling by looking at changes in knowledge before and after counseling. The number of socialization participants was 23 people who were employees from several units. The pre-test results showed that most of the socialization participants still had low knowledge regarding ergonomics are 11 people (47.8%), but after being given information, the post-test results became better, it was found that most of the respondents' knowledge became high, are 21 people (91.3%). The need for understanding and socialization by using promotional media from the Hospital's Health Safety Environment (HSE) Unit and also other intervention programs such as Technology Engineering such as the addition of robotic technology to several types of work, can prevent employees from MSD’s complaints due to ergonomic hazards.